Novel Anthraquinone Derivatives and Their Complexes with Metal Ions with Anticancer Activity: Structure/Redox and Chelation Activity Correlations - Olga Yu. Selyutina; Maya A. Ul’yanova; Olga A. Chinak; Viktor A. Timoshnikov; Lidiya G. Fedenok; Alexander A. Stepanov; Vadim V. Yanshole; Leonid V. Kulik; Sergey F. Vasilevsky; Nikolay E. Polyakov; George J. Kontoghiorghes (Pharmaceuticals)
Background/Objectives: Some specific anthraquinone derivatives (AQs) are known to be used widely as effective chemotherapeutic agents in the treatment of cancer. However, their fundamental shortcoming is the high rate of cardiotoxicity observed in treated patients, which is thought to be caused by the increase in production of reactive oxygen species (ROS) catalyzed by iron and copper. The development of improved AQs and other anticancer drugs with enhanced efficacy but reduced toxicity remains a high priority. The aim of this study was to evaluate the cytotoxic and ROS production effects of chelate iron and copper complexes of two novel AQs, namely 4-hydroxynaphto[2,3-h]cinnoline-7,12-dione (Q2) and 3-(hydroxymethyl)naphto[2,3-h]cinnoline-4,7,12(1H)-trione (Q3). Methods: The chelation ability of Q2 and Q3 was studied using NMR and UV–Vis spectroscopy. Cytotoxicity studies were carried out using the MTT assay. The influence of chelation on ROS production was studied using NMR spectroscopy in linoleic acid micelles. Results: It was found that only Q3 forms complexes with Fe(III) and Cu(II) ions, whereas Q2 does not demonstrate chelating properties. A cytotoxicity study revealed that Fe[Q3]3 significantly decreased the viability of lung cancer A549 cells, while Q3 and Cu[Q3]2 did not demonstrate cytotoxic properties in this cell line. Furthermore, the presence of Q3 lowered the rate of iron-induced lipid peroxidation in linoleic acid micelles. By contrast, Q2 did not influence the rate of lipid peroxidation, probably due to the absence of effective metal chelating ability. Conclusions: The high cytotoxic effects observed with the iron complex of Q3 against cancer cells in combination with a reduced rate of iron induced lipid peroxidation in the presence of Q3, make Q3 and its iron complex promising for further evaluation and use as chemotherapeutic agents in cancer.